2003
DOI: 10.1007/s11664-003-0187-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopant, temperature, and strain rate on the mechanical properties of micrometer gold-bonding wire

Abstract: An experimental study on the thermomechanical properties of microelectronic gold-bonding wires was conducted using high-precision, microforce tensile tests. The load-displacement behavior of three types of gold wire (GL-2 type, FA type, and SR type) was carefully recorded for determining the elastic modulus and stress-strain curves. Tests were conducted with miniature specimens at temperatures ranging from room temperature to 250°C and load rates on the order of 1 mm/min and 10 mm/min. The testing results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 6 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…Generally, alloying elements are added to Au bonding wires to increase wire stiffness [1][2][3] and to increase wire sweep resistance during the epoxy molding compound (EMC) molding process. More alloying elements are added for finer wires.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, alloying elements are added to Au bonding wires to increase wire stiffness [1][2][3] and to increase wire sweep resistance during the epoxy molding compound (EMC) molding process. More alloying elements are added for finer wires.…”
Section: Introductionmentioning
confidence: 99%
“…To satisfy this requirement, gold wires for stud bumping have been developed by adding several doping or alloying elements, which can be classified as either solid solution dopants, such as Pd, Ag, Pt, and Cu, or interstitial dopants, such as Be, Ca, and rare earth elements. 1 Actually, the purposes of doping were to increase wire stiffness, tensile strength for high wire sweep resistance during epoxy molding compound molding process, [1][2][3][4][5]7 and recrystallization temperature for shorter heat-affected zone formation during the electro-flame off process. 6 However, since the electrical resistivity of doped-or alloyed-gold wires was higher than that of pure gold wire (4 N gold wire), many previous studies were performed to investigate the effects of doping elements on mechanical and electrical properties of gold wires.…”
Section: Introductionmentioning
confidence: 99%
“…However, the behavior of wire with respect to the ultrasonic effect is similar to that resulting from heat [17], and the constitutive relation of gold wire considering temperature was measured by Liu et al [18], as shown in Fig. 8.…”
Section: A Fe Model Of Bonding Interfacementioning
confidence: 95%